Perhitungan Poros Roda Belakang Yamaha Jupiter MX 135CC - Dimas Bimantoro; Rizal Hanifi; Viktor Naubnome (Jurnal Ilmiah Wahana Pendidikan, 2022)
Motorcycle is a two-wheeled mode of transportation that is driven by an engine. There are several interrelated components in its use, including a shaft to transmit the rotation generated by the engine and to support balance. The purpose of this study was to determine the calculation of the rear axle of the Yamaha Jupiter MX 135CC. In this study, it can be said that the external load is 401.8 N, where the shaft that receives the bending load will produce a stress that occurs due to the shaft is 108.486 MPa with a diameter of 4.52. It can be said to fail if the stress that occurs is les than the material and the machine element will be said to be safe if the strength of the material is more than the stress that occurs.